Analisis DO, BOD, Dan Total Coliform Sebagai Indikator Kualitas Air Sumber Mata Air Oetbolan Dan Oebonak Di Kota Soe - Oktavina G. LP Manulangga; Hisreidi Funome (Jurnal Kimia dan Ilmu Lingkungan: Chemviro, 2026)
This study aimed to analyze the water quality of Oetbolan and Oebonak springs in Soe City using Dissolved Oxygen (DO), Biochemical Oxygen Demand (BOD), and Total Coliform as indicators. The research employed a descriptive quantitative approach with grab sampling techniques. Water samples were analyzed in the enviromental laboratory using the Winkler method for DO, a five-day incubation method for BOD, and the Most Probable Number (MPN) method for Total Coliform, following the Indonesian National Standards (SNI). The results showed that DO concentrations at Oetbolan and Oebonak springs were 4.12 mg/L and 5.15 mg/L, respectively, which did not meet the established water quality standard (>6 mg/L). In contrast, BOD values were relatively low, measuring 0.7 mg/L at Oetbolan and 0 mg/L at Oebonak, indicating low organic pollution levels and compliance with water quality standards. Total Coliform counts were 13 MPN/100 mL at Oetbolan and 3 MPN/100 mL at Oebonak, which were far below the permissible threshold. These findings indicate that the water quality of both springs is generally good in terms of organic and microbiological aspects; however, limitations were observed in dissolved oxygen availability. This study provides essential scientific information on the condition of local spring water sources and serves as a basis for sustainable water quality monitoring and management